Visually localizing design problems with disharmony maps - Richard Wettel; Michele Lanza (SoftVis'08: Proceedings of the Symposium on Software Visualization, 2008)
Assessing the quality of software design is difficult, as "design" is expressed through guidelines and heuristics, not rigorous rules. One successful approach to assess design quality is based on detection strategies, which are metrics-based composed logical conditions, by which design fragments with specific properties are detected in the source code. Such detection strategies, when executed on large software systems usually return large sets of artifacts, which potentially exhibit one or more "design disharmonies", which are then inspected manually, a cumbersome activity. In this article we present disharmony maps, a visualization-based approach to locate such flawed software artifacts in large systems. We display the whole system using a 3D visualization technique based on a city metaphor. We enrich such visualizations with the results returned by a number of detection strategies, and thus render both the static structure and the design problems that affect a subject system. We evaluate our approach on a number of open-source Java systems and report on our findings.